Analisa Anggaran Pendapatan pada PT Securindo Packtama Indonesia Secure Building Halim Tahun 2020 - Sonny Fransisco Siboro; Armianti Sarita Devita; Anastasia Salempang; Eka Septya Ningsih; Shella Ambarita (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the revenue budget of PT Securindo Packatama Indonesia in 2020. The purpose of this study is to evaluate the suitability between the planned budget and the realization of the company's revenue and to identify factors that influence revenue fluctuations. The type of research used is descriptive research with a quantitative approach. The results of the study indicate significant revenue fluctuations throughout the year which are influenced by operational activities, the number of projects, and the efficiency of vehicle use. There is a difference between the budget and the realization of revenue which indicates the need for improvement in budget preparation. Thus, the company is advised to conduct regular budget evaluations, use more accurate historical data, and improve the accuracy of operational projections.